Obesity and Staphylococcus aureus Nasal Colonization among Women and Men in a General Population - Olsen, Karina; Danielsen, Kjersti; Wilsgaard, Tom; Sangvik, Maria; Sollid, Johanna U. Ericson; Thune, Inger; Eggen, Anne Elise; Simonsen, Gunnar Skov; Furberg, Anne-Sofie (PLoS ONE, 2013)
This paper is part of Karina Olsen's doctoral thesis, available in Munin at http://hdl.handle.net/10037/5596 Background: Obesity and diabetes mellitus (DM) have been linked to increased risk of infections, and Staphylococcus aureus nasal colonization is a major risk factor for developing infections with the microbe. We therefore sought to find whether body mass index (BMI) and waist circumference (WC) could be associated with S. aureus colonization independent of DM. Methodology: S. aureus colonization was assessed by nasal swab cultures among 2,169 women and 1,709 men, aged 30–87 years, in the population-based Tromsø Staph and Skin Study in 2007–08. Height (cm), weight (kg), WC (cm), and glycated haemoglobin (HbA1c,%) were measured. Multivariable logistic regression analyses including information on DM, HbA1c, hormonal contraceptive use and other potential confounders were used. Results: In the female population, each 2.5 kg/m2 increase in BMI was associated with a 7% higher odds of S. aureus nasal colonization (P=0.01). When comparing obese and lean women aged 30–43 years, we observed that BMI $32.5 versus ,22.5 kg/m2 and WC $101 versus ,80 cm was associated with a 2.60 and 2.12 times higher odds of S. aureus colonization, respectively (95% confidence intervals 1.35–4.98 and 1.17–3.85). Among men, high WC was also associated with S. aureus nasal colonization. The associations did not change significantly when the analysis was restricted to participants without signs of pre-diabetes (HbA1c ,6.0%) among women and men, and to non-users of hormonal contraceptives among women. Conclusion: Our results support that obesity is a possible determinant for S. aureus nasal colonization independent of DM, in particular for premenopausal women. The role of obesity at different ages and by sex should be addressed in future prospective studies of S. aureus colonization.